12 VACCINATION UP-TAKE IN DERMATOLOGY PATIENTS OVER THE AGE OF 65 YEARS ON BIOLOGICAL TREATMENT. (25th October 2022) - Egan, A; Farrell, A; Byrne, B; Lynch, M
Abstract: Background: Biologic and immunosuppressive therapies play important roles in the management of a wide variety of dermatologic diseases. However, immunotherapies can negatively affect normal immune functioning, placing these patients at high risk of infection. The strength of the immune system also declines with increasing age. Thus, in accordance with the British Association of Dermatology guidelines (August 2021), patients taking biologic therapy can and should have their covid, influenza and pneumococcal vaccinations. Methods: We conducted a retrospective audit of all patients over the age of 65 years on biological therapy in the dermatology clinic between March 2021 to March 2022. Data on patients covid, influenza and pneumococcal vaccination status was obtained from Dermatology database and patients medical records. Results: A total of 18 patients over the age of 65 years, were on biological therapy in the Dermatology Department, between March 2021 to March 2022. The mean age was found to be 71 years with a standard deviation of 5.2 and there was equal gender distribution. 94% (n=17) of patients had psoriasis and 6% (n=1) had eczema. With regards to biological treatments, 17% (n=3) of patients were on Adalimumab, 11% (n=2) on Etanercept and 28% (n=5) on Cosntyx. 100% (n=18) had all three of their covid-19 vaccines. 50% (n=8) are awaiting their 4th covid vaccination. 94% (n=17) of patients had their influenza vaccine. 66% (n=12) had their pneumococcal vaccination, the patients who had not had their pneumococcal vaccination were recommended and advised to have it. Conclusion: This audit confirms dermatology patients over the age of sixty-five years, are compliant on receiving their covid vaccinations, as recommended by the BAD. However, only 66% of patients had their pneumococcal vaccination and 94% had their influenza vaccine, illustrating the need for educational intervention on the importance of vaccination. This will then be followed by a reaudit next year to complete the audit cycle.